(untitled) (Communications in Computational Physics, 2008)
We present theoretical and experimental studies on the effects of formation properties on seismoelectric conversions in fluid-filled boreholes. First, we derive the theoretical formulations for seismoelectric responses for an acoustic source in a borehole. Then, we compute the electric fields in boreholes penetrating formations with different permeability and porosity, and then we analyze the sensitivity of the converted electric fields to formation permeability and porosity. We also describe the laboratory results of the seismoelectric and seismomagnetic fields induced by an acoustic source in borehole models to confirm our theoretical and numerical developments qualitatively. We use a piezoelectric transducer to generate acoustic waves and a point electrode to receive the localized seismoelectric fields in layered boreholes and the electric component of electromagnetic waves in a fractured borehole model. Numerical results show that the magnitude ratio of the converted electric wave to the acoustic pressure increases with the porosity and permeability increases in both fast and slow formations. Furthermore, the converted electric signal is sensitive to the formation permeability for the same source frequency and formation porosity. Our experiments validate our theoretical results qualitatively. An acoustic wave at a fracture intersecting a borehole induces a radiating electromagnetic wave.